Inference of the impact of insertion sequence (IS) elements on bacterial genome diversification through analysis of small-size structural polymorphisms in Escherichia coli O157 genomes - Ooka, Tadasuke; Ogura, Yoshitoshi; Asadulghani, Md; Ohnishi, Makoto; Nakayama, Keisuke; Terajima, Jun; Watanabe, Haruo; Hayashi, Tetsuya (Genome Research, 2009)
Mobile genetic elements play important roles in the evolution and diversification of bacterial genomes. In enterohemorrhagic Escherichia coli O157, a major factor that affects genomic diversity is prophages, which generate most of the large-size structural polymorphisms (LSSPs) observed in O157 genomes. Here, we describe the results of a systematic analysis of numerous small-size structural polymorphisms (SSSPs) that were detected by comparing the genomes of eight clinical isolates with a sequenced strain, O157 Sakai. Most of the SSSPs were generated by genetic events associated with only two insertion sequence (IS) elements, IS629 and ISEc8, and a number of genes that were inactivated or deleted by these events were identified. Simple excisions of IS629 and small deletions (footprints) formed by the excision of IS629, both of which are rarely described in bacteria, were also detected. In addition, the distribution of IS elements was highly biased toward prophages, prophage-like integrative elements, and plasmids. Based on these and our previous results, we conclude that, in addition to prophages, these two IS elements are major contributors to the genomic diversification of O157 strains and that LSSPs have been generated mainly by bacteriophages and SSSPs by IS elements. We also suggest that IS elements possibly play a role in the inactivation and immobilization of incoming phages and plasmids. Taken together, our results reveal the true impact of IS elements on the diversification of bacterial genomes and highlight their novel role in genome evolution.
10.1101/gr.089615.108